Common variants upstream of KDR encoding VEGFR2 and in TTC39B associate with endometriosis - Valgerdur Steinthorsdottir (Nature Portfolio, 2016)
Endometriosis is a common gynaecological disease but the underlying pathogenesis is poorly understood, however there is a strong familial component. Here the authors conduct a genome wide association study and identify a novel susceptibility locus that correlates with disease severity.